Characterising the discharge cycle of CaCl 2 and LiNO 3 hydrated salts within a vermiculite composite scaffold for thermochemical storage - Eifion Jewell (Energy and Buildings, 2018)
Transpired solar collectors (TSC) are an efficient means of building heating but due to the demand/use mismatch their capabilities are maximised when paired with a suitable storage technology. The Hydration and/dehydration of inorganic salts provides an appropriate energy storage medium which is compatible with the air temperature provided by a conventional TSC (<70 °C). The study reports on technical appraisal of materials which are compatible with building scale energy storage installations. Two salts (CaCl2, and LiNO3) were impregnated into porous vermiculite to form a salt in matrix (SIM). Their performance during the discharge portion of the cycle at high packing density was examined using a laboratory scale reactor. Reactor and exit temperature increases were considerably lower than those predicted from first principles. Peak reactor temperature rises of only 14 °C were observed with a reduction in temperature output from this initial peak over 60 hours. Poor salt utilization resulting from deliquescence near the reactor inlet was identified as being the source of the reduced performance. Changes in reactor size, orientation and cycling between input periods of moist and dry air did not improve reactor performance. The investigation has identified that moist air transit through the packed SIM reactor column is limited to approximately 100 mm from the air inlet. This has implications for reactor design and the operation of any practical building scale installation. Predictions of building scale energy storage capabilities based on simple scaling of laboratory test considerably under estimate the volume and complexity of equipment required.